2016
DOI: 10.1097/dss.0000000000000727
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Collagen-Gelatin Scaffold for the Treatment of Deep Dermal Wounds—An Evaluation in a Minipig Model

Abstract: The new collagen-gelatin scaffold supports and accelerates dermal wound repair compared to untreated control wounds. Nevertheless, wound treatment with the scaffold was only performed on the first day. In further studies, the impact of multiple scaffold applications on full-thickness skin defects should be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Stability and structural design are important determinants for skin tissue engineering, when constructing new dermal substitutes. In previous in vitro and in vivo studies, we already examined the innovative collagen-gelatin scaffold as a scaffold, and the results demonstrated an accelerated and improved dermal wound repair when applied as a single treatment, but even better when applied as multiple treatments [16,22,23]. Moreover, the manufacturing process of the scaffold allows the integration of bioactive substances such as antibiotics and growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…Stability and structural design are important determinants for skin tissue engineering, when constructing new dermal substitutes. In previous in vitro and in vivo studies, we already examined the innovative collagen-gelatin scaffold as a scaffold, and the results demonstrated an accelerated and improved dermal wound repair when applied as a single treatment, but even better when applied as multiple treatments [16,22,23]. Moreover, the manufacturing process of the scaffold allows the integration of bioactive substances such as antibiotics and growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…Topical application provides cell metabolism, migration, and differentiation. Moreover, it can stimulate extracellular matrix secretion and tissue regeneration [ 102 , 103 ]; therefore, shortening treatment time and improving the survival rate of transplants, with better clinical application value [ 104 , 105 , 106 ]. Although most topical applications were used in allogeneic stem cell therapy, other studies’ results were consistent with our systemic review and meta-analysis [ 78 , 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…Next, a sterile semipermeable film was placed on top of every wound. 11 In terms of multiple applications, 6 minipigs received wound dressings on every second day. As the wounds were closing gradually, the size of the applied wound dressings was adapted to the wounds.…”
Section: Methodsmentioning
confidence: 99%
“…Wounds treated with a single application of the nonwoven scaffold 11 showed that the mean epidermal thickness was increased by …”
Section: Epidermal Thicknessmentioning
confidence: 99%
See 1 more Smart Citation